2011
DOI: 10.1016/j.amepre.2010.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Economic Analysis of Physical Activity Interventions

Abstract: Background-Numerous interventions have been shown to increase physical activity, but have not been ranked by effectiveness or cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
181
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(199 citation statements)
references
References 33 publications
2
181
0
4
Order By: Relevance
“…Seven dichotomous questions (1 = yes, 0 = no) were used to assess individual study quality, adapted from Wu et al [33]. The studies were given a score between 0 (lowest quality) and 7 (highest quality) based on a sum calculated for the following: (1) a control group was used, (2) statistically nonsignificant differences existed between baseline characteristics of control and treatment groups, (3) a high-SFA run-in period was used, where all participants were fed the same diet before randomization, (4) measurement tools for data collection were clearly explained in the methods section, (5) all potential confounders were controlled for, (6) study procedures were well defined, and (7) bias was adequately controlled.…”
Section: Methodsmentioning
confidence: 99%
“…Seven dichotomous questions (1 = yes, 0 = no) were used to assess individual study quality, adapted from Wu et al [33]. The studies were given a score between 0 (lowest quality) and 7 (highest quality) based on a sum calculated for the following: (1) a control group was used, (2) statistically nonsignificant differences existed between baseline characteristics of control and treatment groups, (3) a high-SFA run-in period was used, where all participants were fed the same diet before randomization, (4) measurement tools for data collection were clearly explained in the methods section, (5) all potential confounders were controlled for, (6) study procedures were well defined, and (7) bias was adequately controlled.…”
Section: Methodsmentioning
confidence: 99%
“…The best results have come from comprehensive and intensive programmes involving individualised exercise prescriptions, counselling, and educational materials, with follow-up sessions and booster strategies [4]. However, initial increases in physical activity and fitness were not sustained long-term in these studies, and comprehensive intervention programmes have proved the least cost-effective from the public health perspective [5,6]. Notably in the UK, community-based physical activity interventions have been identified as representing a worthwhile investment in terms of healthcare savings [7].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the effects of the stair use campaign were augmented by the use of multicomponent interventions (i.e., stairwell messages + posters). Stair use campaigns using point-of-choice prompts are more cost-effective than other interventions used to increase physical activity 18) . In the follow-up questionnaire survey, 96% of the respondents reported that they "noticed the message banners every day", while 10% of the respondents reported that their "use of the stairs increased due to the message banners".…”
Section: Discussionmentioning
confidence: 99%